A Recirculating Eddy Promotes Subsurface Particle Retention in an Antarctic Biological Hotspot. Issue 11 (11th November 2021) - Hudson, K.; Oliver, M. J.; Kohut, J.; Dinniman, M. S.; Klinck, J. M.; Moffat, C.; Statscewich, H.; Bernard, K. S.; Fraser, W.
Abstract: Palmer Deep Canyon is one of the biological hotspots associated with deep bathymetric features along the West Antarctic Peninsula. The upwelling of nutrient‐rich Upper Circumpolar Deep Water to the surface mixed layer in the submarine canyon has been hypothesized to drive increased phytoplankton biomass, attracting krill, penguins and other top predators to the area. However, observations in Palmer Deep Canyon lack a clear in‐situ upwelling signal, laboratory experiments do not illustrate a physiological response by phytoplankton to Upper Circumpolar Deep Water, and surface residence times are too short for phytoplankton populations to reasonably respond to any locally upwelled nutrients. This suggests that local upwelling may not be the mechanism that links Palmer Deep Canyon to increased biological activity. Previous observations of isopycnal doming within the canyon suggested that a subsurface recirculating feature may be present. Here, using in‐situ measurements and a circulation model, we demonstrate that the presence of a recirculating eddy may contribute to the maintenance of the biological hotspot by increasing residence times at depth and retaining a distinct layer of biological particles. Neutrally buoyant particle simulations showed that residence times increase to ∼175 days at 150 m within the canyon during the austral summer. In‐situ particle scattering, flow cytometry, and water samples from within the subsurface eddy suggest that retained particles are detrital in nature. Our results suggest that this seasonal, retentive feature in Palmer Deep Canyon is important to the retention of biological material and may contribute to the maintenance of this hotspot. Plain Language Summary: Palmer Deep Canyon is an area of high biological activity along the West Antarctic Peninsula. These biological hotspots were once thought to be driven by the upwelling of deep, nutrient‐rich water promoting phytoplankton growth. Previous observations illustrated a lack of upwelling within Palmer Deep Canyon and suggested that a subsurface feature may instead contribute to increased biological activity in the area. We found that a subsurface, closed eddy increases residence times of deep particles over Palmer Deep Canyon. This feature can retain particles through the productive summer months and may be important to the establishment of the biological hotspot. Key Points: Isopycnal doming over Palmer Deep Canyon suggests the presence of a closed, subsurface, cyclonic eddy over the canyon Subsurface eddy increases retention time of simulated particles at depth A persistent, subsurface particle layer, retained by the eddy, consists of individual detritus particles on the order of 70 microns